Complexities of Water Pollution: A Review of Surface Water Contamination in Sri Lanka - M. W. R. Nuwanka; M. D. K. L. Gunathilaka (International Journal of Environment, Engineering and Education, 2023)
Water is indispensable for sustaining life, food production, economic growth, and well-being. However, the growing population and industrialization have intensified the demand for freshwater, posing significant challenges to water resources in Sri Lanka. This review paper focuses on understanding the types and causes of water pollution, with a particular emphasis on surface water pollution, as well as exploring preventive measures in the context of Sri Lanka. Given its severe consequences and the global issue of water scarcity, water pollution has gained attention from researchers, scientists, and organizations. Surface water bodies, such as lakes and rivers, face pollution primarily due to inadequate management of sewage and industrial effluents. Insufficient sanitation facilities in low-income settlements further exacerbate the problem, affecting the country. Despite existing regulations, the lack of monitoring allows improper waste disposal practices to persist. Rural areas experience groundwater contamination from agrochemicals, while urban areas suffer from pollution caused by domestic sewage. Considering the limited resources, prioritizing pollution prevention proves to be a cost-effective approach. Effective control measures are required to address marine pollution, adversely impacting fisheries and tourism. Recognizing the interconnected nature of all types of water pollution is crucial, as they contribute to ecological degradation. To safeguard water resources, several measures must be implemented. These include improving sewage treatment systems, implementing better management practices for industrial effluents, prioritizing pollution prevention strategies, and strengthening monitoring mechanisms. Prioritizing water resource preservation will safeguard ecosystems, support sustainable development, and ensure well-being.